A Holocene record of environmental change from Río Zeballos, central Patagonia - (:unkn) unknown (SAGE, 2017)
There are few continuous palaeoenvironmental records spanning the Holocene in Andean Southern Patagonia near the Northern Patagonian Ice Field (~47°S). Insights into the environmental context for human-landscape interactions have relied mostly on data extrapolated from distant extra-Andean locations that suggest limited environmental change during the Holocene. La Frontera (46°52’S), a high altitude site on the southern beech forest-steppe ecotone boundary in the Río Zeballos valley provides lithostratigraphical and palaeoecological evidence, constrained by 14C dating and tephrochronology, for dynamic environmental change during the last ~8000 years. An initial amelioration in environmental conditions after c. 8210 cal. BP was followed by a reversal to colder conditions between c. 7420 and 6480 cal. BP, coincident with initial human occupation within the Paso Roballos and Lago Pueyrredón basin. Between c. 6480 and 3700 cal. BP the woodland / steppe composition continued to fluctuate in response to climatic change. After c. 3700 cal. BP a gradual shift to more stable and temperate conditions, punctuated by increased fire activity, is contemporary with the later phases of human occupation extending up into the Paso Roballos-Río Zeballos corridor.
Fil: McCulloch, Robert D.. University of Stirling. Biological and Environmental Sciences; Escocia.
Fil: Figuerero Torres, María José. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Arqueología; Argentina.
Mengoni Goñalons, Guillermo L.. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Arqueología; Argentina.
Fil: Barclay, Rebecca. University of Stirling. Biological and Environmental Sciences; Escocia.
Keywords: Central Patagonia; Holocene; Palaeoenvironments; Pollen analysis; Tephrochronology; Arqueología